Development of Creative Thinking Level Assessment Instruments with Rasch Model Approach in Football Lectures - Wawan Junresti Daya; Mohd. Adrizal; Reza Hadinata; Ely Yuliawan; Boy Indrayana (CV. Creative Tugu Pena, 2025)
The instrument of creative thinking skills in the game of football is an assessment instrument in football sports courses. This instrument is used to measure students' creative thinking skills. This research aims to: (a) produce a feasible and qualified instrument to be used in the assessment of the level of creative thinking with the Rasch model approach in the Football course, and (b) find out the characteristics of the assessment instrument of the level of creative thinking with the Rasch model approach in the Football course. In this study, a modified development model based on the Wilson, Orindo, and Antonio model was used. This model has the following stages: a) compiling the initial design of the product; b) prepare research instruments for the initial design of the product; c) product validation and trial; and d) application in testing the products produced. This study uses a modified development model from Wilson, Orindo, and Antonio, which consists of three stages: (1) designing the test, (2) conducting test trials, and (3) conducting test measurements. The population in this study is 155 students who take football courses with total sampling techniques. The test instrument product is assessed by experts through a content validation sheet, where there are 2 experts, namely measurement experts (test construction experts) and sports education experts (material experts). The results of the analysis in this study show that the test instrument is feasible and qualified to be used in measurement. The conclusions in this study are a) The test instrument has been proven to be valid by experts; b) The test instrument is in the high category based on the function of information.